2017
DOI: 10.1007/s00406-017-0838-2
|View full text |Cite
|
Sign up to set email alerts
|

Donepezil effects on cholesterol and oxysterol plasma levels of Alzheimer’s disease patients

Abstract: Cholesterol is an essential component in the structure and function of cell membranes and has been associated with the major pathological signatures of Alzheimer's disease (AD). To maintain brain cholesterol homeostasis, it is converted into 24(S)-hydroxycholesterol (24OHC) which can be driven through the blood-brain barrier. Several studies have already described a decrease in 24OHC and an increase of 27(S)-hydroxycholesterol (27OHC) in AD, as a reflection of disease burden, the loss of metabolically active n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 69 publications
2
16
0
Order By: Relevance
“…This study has also claimed that the levels of 24‐hydroxycholesterol and cholesterol 24‐hydroxylase are both decreased in the post‐mortem AD brain along with downregulation of Sirtuin 1 . Thus, the clear majority of experimental data, including some elegant molecular genetic studies, tends to support the protective effect of this compound against AD pathogenesis, although a few studies have indicated the neurotoxic potential of 24‐hydroxycholesterol . In brief, the decreased 24‐hydroxycholesterol level in peripheral circulation in AD cases observed in different studies, including the present one, is very much consistent with experimental data and, further, it suggests that the deficiency of this oxysterol has a role in AD pathogenesis.…”
Section: Discussionsupporting
confidence: 90%
“…This study has also claimed that the levels of 24‐hydroxycholesterol and cholesterol 24‐hydroxylase are both decreased in the post‐mortem AD brain along with downregulation of Sirtuin 1 . Thus, the clear majority of experimental data, including some elegant molecular genetic studies, tends to support the protective effect of this compound against AD pathogenesis, although a few studies have indicated the neurotoxic potential of 24‐hydroxycholesterol . In brief, the decreased 24‐hydroxycholesterol level in peripheral circulation in AD cases observed in different studies, including the present one, is very much consistent with experimental data and, further, it suggests that the deficiency of this oxysterol has a role in AD pathogenesis.…”
Section: Discussionsupporting
confidence: 90%
“…Aβ is believed to be the essential trigger of AD pathology. Evidence has shown that 27‐OHC could increase the levels of Aβ and induce endoplasmic reticulum stress, a cellular response that is implicated in AD . It is also demonstrated in in vitro studies that Aβ could be released after 27‐OHC treatment .…”
Section: Discussionmentioning
confidence: 99%
“…Gamba et al reports that plasma levels of 27‐OHC are significantly reduced in patients with dementing disorders compared to non‐demented subjects . Moreover, it is pointed that no differences were found in the plasma levels of 27‐OHC between AD patients and the controls . The reason for this divergence might be related to the different genetic backgrounds of the population, the proportion of different stages of cognitive decline and even the distribution of age, sex and education .…”
Section: Discussionmentioning
confidence: 99%
“…After 6 months of treatment, there was a discrete increase in cholesterol levels, but no change in 24(S)-hydroxycholesterol levels. Although Costa et al [8] suggest a role of disturbed cholesterol turnover in AD pathogenesis, further studies using larger populations are needed.…”
mentioning
confidence: 97%
“…Interestingly, there is considerable evidence suggesting a relationship between the degree of brain atrophy and plasma levels of the cholesterol metabolite 24(S)-hydroxycholesterol [7]. In this issue, Costa et al [8] found decreased plasma levels of 24(S)-hydroxycholesterol in probable AD patients (n = 30) compared with healthy controls (n = 33), whereas plasma levels of 27(S)-hydroxycholesterol and total cholesterol were not altered. Furthermore, the presence of an ApoE4 allele was not associated with cholesterol, 24(S)-hydroxycholesterol or 27(S)-hydroxycholesterol.…”
mentioning
confidence: 97%